El estado inka en el valle de Acarí de la costa sur del Perú - Valdez, Lidio M. (2024)
Until recently, it was thought that the Inka state’s interference in regions that accep- ted peaceful incorporation was minimal. It was argued that beyond the provincial cen- ters established by the Cusco rulers, Inka interference was almost negligible, apparently because the state did not see it necessary to interfere with a population that accepted his presence. Recent archaeological research carried out in the Acarí Valley on the south coast of Peru shows that the Inka occupation resulted in significant changes, such as the establishment of new settlements, to which the local people appear to have been relocated. Thus, the new evidence demonstrates that people who did not offer any resistance to the Inka expansion were affected by the decisions adopted by the Cusco authorities.